WOMEN OF FATE: POWER AND POLITICS OF WOMEN IN DUNE, DUNE MESSIAH, AND CHILDREN OF DUNE - Verma, Gargi; Sharma, Parvanshi (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The Dune saga by Frank Herbert is a science fiction genre that puts feminine power as the core of the myth-making epic. Throughout Dune (1965), Dune Messiah (1969), and Children of Dune (1976), women are a lot more than just empowering their male characters. They build dynasties, direct human evolution, and the religious and ideological frameworks that keep the Imperium united. The paper observes the overlapping roles of the most powerful female characters in both political and psychological terms. This narrative counters the masculinity of imperial power. By applying feminist theory, psychoanalysis, and posthumanist feminism, this paper shows how Herbert has portrayed the gender relations in a nuanced way. It reveals the varied spectrum of power in terms of memory, motherhood, and embodied power. The Bene Gesserit comes out as a posthuman survivalist tool that constructs possible futures by embedding historical narratives into the female body. The paper concludes that the female characters of the DUNE saga are critical instruments of continuity, resistance, and change.